Efektivitas Ekstrak Bunga Telang (Clitoria ternate L.) sebagai Inhibitor Korosi Ramah Lingkungan dalam Media Asam - Ferawati, Yohana Fransiska; Sajida, Gita Nur; Krista, Gustin Mustika; Sari, Hermin Kartika; Taufiqurohim, Teguh; Sihombing, Rony Pasonang (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Corrosion is an indicator of metal quality degradation. One method to prevent corrosion is by using corrosion inhibitors. Corrosion inhibitors are compounds added to corrosive media to reduce the rate of corrosion. The use of environmentally friendly natural inhibitors such as butterfly pea flower extract can serve as an alternative to hazardous chemical inhibitors. This study aims to evaluate the performance of natural inhibitors derived from butterfly pea flower extract in preventing corrosion of low-carbon steel plates. The experiment was conducted in 0.25 N and 0.5 N HCl media with inhibitor concentrations ranging from 100 to 1000 ppm. The steel plates were immersed for 7 days. The parameters studied were corrosion rate and inhibitor efficiency. The results showed that higher inhibitor concentrations led to lower corrosion rates in both acidic media. The lowest corrosion rate was obtained at 1000 ppm inhibitor concentration, with a value of 228.70 mdd and an efficiency of 32.12% in 0.5 N HCl solution, while in 0.25 N HCl solution, the lowest corrosion rate was 156.69 mdd with an efficiency of 30.66%. This study indicates that butterfly pea flower extract has potential as an effective corrosion inhibitor for low-carbon steel plates in an acid medium. This finding supports its application as a sustainable alternative for corrosion control.